Identification of water compartments in spinal cords by 2H double quantum filtered NMR. (20th December 2020) - Eliav, Uzi; Shinar, Hadassah; Navon, Gil
Abstract : In 2 H double quantum filtered (DQF) NMR, the various water compartments are characterized by their different residual quadrupolar interactions. The spectral separation between the different signals enables the measurement of the relaxation of each compartment and the magnetization transfer (MT) between them. In the current study, five water compartments were identified in the 2 H DQF spectra of porcine spinal cord. The most prominent signal was the pair of satellites with a quadrupolar splitting of about 550 Hz. 2 H DQF MRI optimized for the 550 Hz quadrupolar splitting indicated that this signal originated mainly from the white matter and it was assigned to the myelin water. This splitting does not change upon changing the orientation of the spinal cord relative to the magnetic field, indicating a liquid crystalline nature. Another site exhibiting splitting of about 1500 Hz was assigned to collagenous connective tissue. The narrow central peak was assigned to a combination of intra‐ and inter‐axonal water. The assignment of the other two sites is not certain and requires further study. The rates of MT between the various sites were recorded. Abstract : In 2 H double quantum filtered (DQF) NMR, the various water compartments are characterized by their different residual quadrupolar interactions. Five water compartments were identified in the 2 H DQF spectra of porcine spinal cord and the water exchange between them was studied. The most prominent signal with a quadrupolar splitting of about 550 Hz stems from the myelin water. This splitting does not change upon changing the orientation of the spinal cord relative to the magnetic field, indicating liquid crystalline nature.